2016
DOI: 10.1186/s40813-016-0027-0
|View full text |Cite
|
Sign up to set email alerts
|

Production parameters and pig production cost: temporal evolution 2010–2014

Abstract: BackgroundThe assessment of the cost of production and the relative weight of the different production parameters is very important in pig farming. The goals of the present work were 1) to describe reliable reference values for production parameters and pig production cost from 2010 to 2014, 2) to describe their temporal evolution and 3) to determine the influence of the pig company size on them. Between 61 and 107 pig production companies from Spain were included in this study from 2010 to 2014. These compani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 9 publications
3
36
0
2
Order By: Relevance
“…The estimated holding sizes fit into the observed trend, even though higher values have been reported from other countries for estimates of the number of weaners based on the number of sows per holding [30]. Nevertheless, these values might have changed since 2006.…”
Section: Discussionsupporting
confidence: 60%
“…The estimated holding sizes fit into the observed trend, even though higher values have been reported from other countries for estimates of the number of weaners based on the number of sows per holding [30]. Nevertheless, these values might have changed since 2006.…”
Section: Discussionsupporting
confidence: 60%
“…On the other hand, a worsening in performance as the size of the herd increases has been reported previously. In a study analysing production parameters and production cost over time (2010-2014) in Spain, Rocadembosch et al [39] concluded that herd size affected negatively most performance indicators, including ADG in nursery and nishing stages, as also found in this other study [40].…”
Section: Discussionsupporting
confidence: 74%
“…Pig meat represents 9% of the total EU agricultural output and is the major type of meat produced in the EU-28 (Eurostat, 2015). Intensification of porcine farming in Europe has improved production performance (Rocadembosch et al, 2016;Eurostat, 2017). Yet, challenges linked to this intensification have been described and have led to the introduction of the term "production diseases" to describe this phenomenon (Nir, 2003;Clark et al, 2016).…”
Section: Introductionmentioning
confidence: 99%